Aftershock Rate and Pore Fluid Diffusion: Insights From the Amatrice‐Visso‐Norcia (Italy) 2016 Seismic Sequence. Issue 1 (25th January 2019) - Albano, Matteo; Barba, Salvatore; Saroli, Michele; Polcari, Marco; Bignami, Christian; Moro, Marco; Stramondo, Salvatore; Di Bucci, Daniela
Abstract: We developed a numerical model by using only early and unreviewed data and information related to the 2016 M w 6 earthquake in central Italy to quickly evaluate the pore pressure contribution to the aftershock release after a severe mainshock. Moreover, a computational procedure is proposed for discussing if and how such an approach could be useful in the management of a seismic crisis. The two‐dimensional finite element model in this study is based on poroelastic theory and includes a planar seismogenic fault. The model geometry and parameters are based on data collected from the literature before the mainshock. The dip and depth of the seismogenic fault are based on preliminary information from focal mechanisms and related fault inversions. The fault slip is calibrated with synthetic aperture radar interferometric data, and the hydraulic properties of the medium are progressively calibrated based on routine aftershock data collected during the sequence. The procedure proposed here can be efficiently applied in a diverse range of cases depending on data availability. Typically, the available "ingredients" allow for a quick, simplified analysis to be conducted rapidly. The simulation results show that early information and routine data are useful in developing and calibrating a model that can rapidly describe the approximate temporal evolution of overpressured conditions, which represent a crucial driving mechanism in the occurrence of aftershocks. These findings highlight the need to adequately consider time‐dependent poroelastic effects when modeling postseismic scenarios and predicting the spatiotemporal evolution of the stresses following a large earthquake. Key Points: A quick evaluation of the pore pressure contribution to the aftershock release after the August 2016 Amatrice earthquake has been performed Poroelastic modeling shows that the postseismic fluid flow diffusion is related to the daily aftershock rates Early information and data are useful in developing a model to describe the approximate temporal evolution of overpressured conditions